Sulforaphane Ameliorates the Intestinal Injury in Necrotizing Enterocolitis by Regulating the PI3K/Akt/GSK-3β Signaling Pathway - Zhong-Kun Bao; Yan-Hong Mi; Xiao-Yu Xiong; Xin-Hong Wang (Canadian Journal of Gastroenterology and Hepatology)
Objective. Necrotizing enterocolitis (NEC) is a serious neonatal disease; this study aims to investigate the role of sulforaphane (SFN) in NEC-induced intestinal injury. Methods. An animal model of NEC was established in newborn mice and intragastrically administrated with SFN; then, the general status and survival of the mice were observed. H&E staining was used to observe the pathological changes of intestinal tissues. ELISA, immunohistochemical staining, and flow cytometry assays were used to detect the levels of inflammatory factors, including TNF-α, IL-6, and IL-17, the expression of Bax, Bcl-2, TLR4, and NF-κB, and the percentages of the Th17 and Treg cells, respectively. GSK-3β expression levels were measured by immunofluorescence. IEC-6 and FHC cells were induced with LPS to mimic NEC in vitro and coincubated with SFN; then, the inflammatory factor levels and cell apoptosis rate were detected. Finally, Western blot was used to assess the expression of PI3K/Akt/GSK-3β pathway-related proteins in vitro and in vivo. Results. SFN improved the survival rate of NEC mice during modeling, alleviated the severity of the intestinal injury, and reduced the proportion of Th17/Treg cells. SFN could inhibit TLR4 and NF-κB levels, decrease the release of inflammatory factors TNF-α and IL-6, suppress Bax expression, increase Bcl-2 expression, and inhibit apoptosis both in in vitro and in vivo models of NEC. Meanwhile, SFN regulated the expression of PI3K/Akt/GSK-3β pathway-related proteins in vitro and in vivo. Conclusion. SFN relieved the inflammatory response and apoptosis by regulating the PI3K/Akt/GSK-3β signaling pathway, thereby alleviating NEC in model mice and cells.